Remaining Tasks after Passing of the Retirement Age Extension Bill - Soo Kyeong Hwang (Korea Development Institute (KDI), 2013)
Having made a retirement age of 60 mandatory through the revision of the law this time has obviously arranged a turning point in relation to utilization of middle/high-aged human resources. But, extension of retirement age which does not accompany wage adjustment may increase corporate labor costs, reduce new employment of youngsters, and may rather act as a cause for layoff of middle/high-aged workers. - The retirement age of 60 will be made mandatory in Korea in stages from 2016. - Throughout our society, a bond of sympathy has been formed to some extent that the current retirement age system which retires workers at an excessively early age is not desirable for individual workers and the national economy in view of the fast aging trend of our society. - A mandatory retirement system is an employment practice mainly found in Japan and Korea where seniority-based personnel practice is common. - Seniority wage is a wage system wherein the economic rationality is pursued by quadrating lifetime wage with lifetime productivity on the premise of long-term employment. - As the cycle of production is reduced and change in technology progresses rapidly, the likelihood that the gap between a life-long increase in the wage and life-long increase in the productivity is further amplified has increased. - Companies have come to induce early retirement of middle-aged/aged workers in diverse forms, and, as a result, the long-term employment relation itself which has been the base of the seniority wage is in a threatening situation. - As the workers may experience rapid reduction in the income during the extended employment period in the case of the wage peak system, it may be more desirable to adjust the wage plan to be similar to the actual productivity still maintaining the incentive for long-term continuous service. - It is a general analysis that the substitutive relation between employment of the aged and youth is not apparent in the macroeconomic aspect. - Competition between generations can partially exist for good quality jobs in public corporations and large companies. - The issue of fairness between the beneficiaries and non-beneficiaries of the extension of the retirement age should be taken into account. - The policy to promote employment stability of middle-aged/aged workers relying on the retirement age system has a limit. - It is required to strengthen the coordination and mediation function of the National Labor Relations Commission in relation to the adjustment of the wage system before the extension of the retirement age is enforced. - In the mid/long-term, it is required to make efforts to restructure the retirement age system as a compulsory retirement system into an arbitrary or social retirement age system.
Keywords: 330